(untitled) (The Agriculturists, 2010)
Sesarmid crabs are reported to dominate the Indo West-Pacific mangroves and consume huge amounts of mangrove leaves and detritus. Neosarmatium trispinosum Davie (1994) is common in the landward mangroves of the Ryukyu Islands in southern Japan. Stomach contents of the crabs collected from Okinawa, Miyako and Iriomote Islands showed that their diet consisted of mainly mangrove leaves with small amounts of sediments indicating that N. trispinosum is primarily detritivorous. The feeding preference of N. trispinosum was investigated by offering three types (green, yellow and brown) of Bruguiera gymnorrhiza leaves. Crabs were found to prefer brown leaves than the green or yellow ones. Consumption rate of brown leaves was significantly higher (p<0.0001) in cases where green, yellow and brown leaves were provided together, than when provided separately. The C/N ratio shows that the burrow sediments had C/N ratios 2/3 times lower than that of leaves, indicating that mangrove sediments could have higher nutritional value than mangrove leaves.